2020
DOI: 10.12688/f1000research.23713.2
|View full text |Cite
|
Sign up to set email alerts
|

A dataset for the perceived vulnerability to disease scale in Japan before the spread of COVID-19

Abstract: The COVID-19 outbreak is a worldwide medical and epidemiological catastrophe, and the number of psychological studies concerning COVID-19 is growing daily. Such studies need baseline data from before the COVID-19 outbreak for comparison, but such datasets have not yet been accumulated and shared. Here, we provide a dataset on the perceived vulnerability to disease scale for 1382 Japanese participants obtained through an online survey conducted in 2018 that will be useful for comparison with current or post-COV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Therefore, we retained the 13-item structure found in Study 2 and compared it with other alternative models. As alternative models, we adopted the unifactorial model, which is widely reported in the literature (Alexandre et al, 2020;Stangier et al, 2021;Yamada et al, 2020), as well as the trifactorial and tetrafactorial models, as suggested by the parallel analysis and the Kaiser and Cattel criteria, respectively (Table 3).…”
Section: Confirmatory Factorial Analysismentioning
confidence: 99%
“…Therefore, we retained the 13-item structure found in Study 2 and compared it with other alternative models. As alternative models, we adopted the unifactorial model, which is widely reported in the literature (Alexandre et al, 2020;Stangier et al, 2021;Yamada et al, 2020), as well as the trifactorial and tetrafactorial models, as suggested by the parallel analysis and the Kaiser and Cattel criteria, respectively (Table 3).…”
Section: Confirmatory Factorial Analysismentioning
confidence: 99%
“…The PVD scale reflects 'perceived infectability', which is related to the beliefs of one's own susceptibility to infectious diseases, and 'germ aversion', which is related to an awareness of discomfort in situations with a high likelihood of infection from a pathogen. We measured the PVD scale scores and statistically compared the PVD scale scores collected in the present experiment with those collected before COVID-19 situation [18] as a check on the growing concern for infection. The comparison of the PVD scores between the current and non-pandemic situations should advance the discussion of the effect of self-related reminders based on the comparisons.…”
Section: Methodsmentioning
confidence: 99%
“…In this case, to confirm that there was a significantly growing concern for infection during the COVID-19 pandemic, we used the PVD scale [16,17]. We used a dataset collected before COVID-19 that has been published elsewhere [18]. This dataset is not related to the main purpose of this study, the IP-intention scale, or the IP-behaviour scale, and none of the authors conducted any statistical analysis on this dataset.…”
Section: Quality Checks For Providing a Fair Testmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the Covid-19 pandemic, people have been exposed to alarming mass media news about those infected, which caused them to face the fear of getting the virus, hence, stress and anxiety (Gonzales-Olmo et al, 2020). Thus, people have become more strictly bound to hygiene rules than ever before resulting in acting with the concern of getting infected (Yamada et al, 2020). This may have caused an increase in the existing perceived vulnerability due to the Covid-19 crisis.…”
Section: H3 Pandemic Fatigue Moderates the Relationships Between Empathetic Responses Towards Psa Characters And Altruistic Feelingsmentioning
confidence: 99%